Study Of Engine Performance And Emissions Characteristics Of A SI Engine Fueled With Different Octane Rating Gasoline - Wan, Dun Ye (Universiti Sains Malaysia, 2018)
Due to world crude oil price hike in the recent years, many countries have experienced increase in gasoline price. In Malaysia, where gasoline is sold in three grades; RON95 and RON97 and RON100 fuel price are regulated by the government, gasoline price has been gradually increased since 2009. The effect of gasoline RON95, RON97 and RON100 on performance and exhaust emissions in spark ignition engine was investigated on a representative engine: 1.298L, 4-cylinder K3-VE engine with CR 10:1. The engine was run at constant speed between 1000 and 4000 rpm with 1000 rpm increment at various loading conditions. The SI engine was connected to eddy current dynamometer and controller system with the exhaust gas analyser to determine engine performance and exhaust emissions characteristic. The experimental results showed that the using gasoline with octane grades higher than the requirement of an engine will decrease the engine performance. On average, the brake power and thermal efficiency for the SI engine fuelled with RON 95 is higher than that of gasoline RON 97 and RON 100 by 0.74% and 0.61% respectively, and improvement of BSFC by 4.1% and 2.6%. In general, the exhaustemission profiles for NOx and CO of the engine improved for RON 100 by 9% and 4.37% respectively. On the other side, the HC and CO2 emissions concentration of gasoline RON 100 is lower than that of RON octane 95 by 26.5% and 1.9% respectively. RON 95 can deliver high performance and efficiency in both loading conditions whereas RON 100 fuel produced the lowest in compared to RON 95 and RON 97 fuels. Therefore, from economically view point, it is recommended that RON 95 be used in maintain the good performance with this type of engine. Besides, from this study, it proofs that higher RON gasoline not necessarily beneficial on engine power and fuel economy especially when the higher RON fuel was run with the moderate compression ratio engine. One of the reason that higher RON gasoline is suggest to be use is because of the advantage of RON 97 and RON 100 shown in the aspect of effectively reduction on the emissions of polluting gases CO and HC.